Fluorescent material layering method
By mixing red and green fluorescent materials with curable resins and forming a layered structure through centrifugation or external field application, the problem of self-absorption of fluorescent materials in white LEDs is solved, luminescence efficiency is improved and the manufacturing process is simplified.
Patent Information
- Application Number
- CN202411477668.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-21
- Filing Date
- 2024-10-22
- Publication Date
- 2025-04-25
AI Technical Summary
In the existing white LEDs, the mixture of red fluorescent materials and green fluorescent materials has problems with light self-absorption, resulting in low luminescence efficiency.
By mixing the red fluorescent material and the green fluorescent material with the curable resin, a binder mixture is made, and the red fluorescent material and the green fluorescent material are separated by methods such as centrifugation or external field application to form a layered structure, and finally the layered structure is cured onto the substrate.
Reduced self-absorption of light by red and green fluorescent materials, improves the luminous efficiency of LEDs, and simplifies the manufacturing process, avoiding multiple setup and curing steps.
Smart Images

Figure CN119894193A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of light conversion materials, and in particular to a layering method of fluorescent materials. Background Art
[0002] In the application of white light emitting devices (LEDs), one method is to mix red fluorescent materials and green fluorescent materials to form a fluorescent material mixture. Then, a blue light-emitting chip is used as a light source to excite the fluorescent material mixture. It is very important to reasonably set the mixing ratio and concentration relationship of the red fluorescent material and the green fluorescent material in the fluorescent material mixture, because the final transmitted light must be white light.
[0003] The fluorescent material mixture formed by mixing red fluorescent material and green fluorescent material has the problem of self-absorption of light, resulting in low luminous efficiency of the fluorescent material mixture. Therefore, we need a method for manufacturing LEDs that can improve the excitation efficiency of fluorescent materials, thereby effectively improving the luminous efficiency of light-emitting devices. Summary of the invention
[0004] This summary is intended to introduce some concepts that are further developed in the detailed description below. This summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used as an aid in limiting the scope of the claimed subject matter.
[0005] In one aspect, embodiments disclosed herein relate to the following aspects: A method of manufacturing a layered structure, the method comprising mixing a red fluorescent material and a green fluorescent material with a curable resin to form an adhesive mixture; placing the adhesive mixture on a substrate; centrifuging the adhesive mixture to separate the red fluorescent material and the green fluorescent material to form a layered structure; and curing the layered structure on the substrate.
[0006] In another aspect, the embodiments disclosed herein relate to a method for manufacturing a layered structure, the method comprising: mixing a red fluorescent material and a green fluorescent material with a curable resin to form an adhesive mixture; setting the adhesive mixture on a substrate; applying an external field to the adhesive mixture to separate the red fluorescent material and the green fluorescent material to form a layered structure; and curing the layered structure onto the substrate.
[0007] In another aspect, the embodiments disclosed herein are related to a method for manufacturing a layered structure, the method comprising: mixing a red fluorescent material and a green fluorescent material with a curable resin to form an adhesive mixture; setting the adhesive mixture on a substrate; phase-separating the adhesive mixture to separate the red fluorescent material and the green fluorescent material to form a layered structure; and curing the layered structure onto the substrate.
[0008] In another aspect, the embodiments disclosed herein relate to a layered structure made by the above method for making a layered structure.
[0009] Other aspects and advantages of the claimed subject matter will be apparent from the following description and appended claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] The drawings constituting part of the present application are used to provide a further understanding of the present disclosure. The exemplary embodiments of the present disclosure and their descriptions are used to explain the present disclosure and do not constitute an improper limitation on the present disclosure. In the drawings:
[0011] Figure 1 is a schematic diagram of a hierarchical structure according to one or more embodiments.
[0012] Figure 2 A( Figure 2 ) is an example of an LED structure according to one or more embodiments.
[0013] Figure 2 B( Figure 2 ) is an example of a hierarchical structure according to one or more embodiments. DETAILED DESCRIPTION
[0014] White light LEDs can be made from a mixture of red and green fluorescent materials that produce white light when excited by blue light. It can be advantageous to layer the red and green structures so that the red fluorescent material is closer to blue light than the green fluorescent material to minimize the self-absorption of light by the mixture of red and green fluorescent materials. Traditional methods for making such devices involve preparing two separate resin mixtures, one including red fluorescent materials and the other including green fluorescent materials, and then laying these materials separately on a substrate. This method can be cumbersome, requiring two separate steps to set up the resin mixtures, and each mixture must be cured. In contrast, the methods described herein include preparing a mixture containing red and green fluorescent materials and then separating these materials by chemical or physical methods to form a layered structure. These methods can avoid multiple setting and curing steps while still providing LEDs with high light efficiency. These methods also provide useful layered structures for LED applications.
[0015] In one aspect, embodiments disclosed herein relate to a method for preparing a light-converted LED package, comprising mixing at least two fluorescent materials and a curable resin to obtain an adhesive mixture, and applying the adhesive mixture to an LED chip in one step. The fluorescent materials can then be separated into different layers by chemical or physical methods. A fluorescent material that emits a long peak wavelength may be closer to a substrate than a fluorescent material that emits a short peak wavelength. Thus, the two fluorescent materials are located in different layers. Once separated into different layers, the structure can be cured to obtain a light-converted LED package.
[0016] In this disclosure, reference will be made to red and green fluorescent materials. Red fluorescent materials emit photons with wavelengths in the red portion of the visible spectrum, and green fluorescent materials emit photons with wavelengths in the green portion of the visible spectrum. Red fluorescent materials may also be referred to as "long wavelength" materials, and green fluorescent materials may be referred to as "short wavelength" materials. The two terms may be used interchangeably.
[0017] According to one or more embodiments, a light conversion LED package includes a layered structure. Figure 1 The layered structure 110 includes a red fluorescent material 130 , a green fluorescent material 140 , and a curable resin 150 .
[0018] As will be described in more detail below, the present disclosure relates to layers or stratifications of different wavelength fluorescent materials.
[0019] For the purposes of the present disclosure, a layer refers to an area (i.e., a red layer) containing a majority of red fluorescent material and an area (i.e., a green layer) containing a majority of green fluorescent material in a layered structure. For example, based on the total volume of fluorescent material in the red layer, the red layer may contain at least 50%, 55%, 60%, 70%, 80%, 90%, 95%, 98%, 99% or 100% by volume of red fluorescent material. Similarly, based on the total volume of fluorescent material in the green fluorescent layer, the green fluorescent layer may contain at least 55%, 60%, 70%, 80%, 90%, 95%, 98%, 99% or 100% by volume of green fluorescent material. The area where the red fluorescent material and the green fluorescent material contact each other (also referred to as the "middle area") may be a mixture of red fluorescent material and green fluorescent material. However, according to an embodiment of the present disclosure, the amount of red fluorescent material in the middle area may be greater than the amount of green fluorescent material.
[0020] In one or more embodiments, the layered structure 110 is located on top of a substrate 120. The substrate can be any substrate known in the art for LEDs. According to one or more embodiments, the substrate is a plastic printed circuit board. Suitable substrate materials include polyphthalamide (PPA), poly(1,4-cyclohexane diglycidyl terephthalate) (PCT), epoxy molding compound (EMC), and combinations thereof.
[0021] In one or more embodiments, the hierarchical structure 110 has a red fluorescent material 130, described as red fluorescent dots 130 in Figure 1 . The red fluorescent material 130 can be a phosphor or a quantum dot. The quantum dot can be a perovskite quantum dot, a carbon dot, a graphene quantum dot, a semiconductor nanocrystal quantum dot, and combinations thereof. In certain embodiments, the red fluorescent material 130 is spherical or near-spherical. In some embodiments, the red fluorescent material 130 has a narrow size distribution, as measured by photoluminescence spectroscopy, with a full width at half maximum (FWHM) equal to or less than 30 nanometers. Non-limiting examples of the red fluorescent material 130 are red K2SiF6:Mn 4+ phosphor or red CdSe / ZnS quantum dots. The red fluorescent material 130 can include A2MF6:Mn 4+ red phosphors, where A is an alkali metal and M is Si, Ge, Sn, Ti, Zr, or Hf (e.g., K2SiF6:Mn 4+ ). The red fluorescent material 130 can further include MSe 1-x S x :Eu, where M is at least one of Mg, Ca, Sr, Ba, and Zn, and 0 < x < 1.0. Red and green fluorescent materials are well known in the art and are readily available on the market. According to one or more embodiments, the emission peak wavelength of the red fluorescent material 130 is between 600 and 690 nanometers.
[0022] In one or more embodiments, the layered structure 110 has a green fluorescent material 140. The green fluorescent material 140 can be a phosphor or a quantum dot. The quantum dots can be perovskite quantum dots, carbon dots, graphene quantum dots, semiconductor nanocrystal quantum dots, and combinations thereof. In certain embodiments, the green fluorescent material is spherical or approximately spherical. Exemplary quantum dots include, but are not limited to, Group II-IV semiconductors such as CdS, CdSe, CdS / ZnS, CdSe / ZnS, or CdSe / CdS / ZnS, Group II-VI semiconductors such as CdTe, ZnSe, ZnTe, ZnS, HgTe, HgS, HgSe, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, Cd ZnSTe, CdHgSe, CdHgSe, CdHgSeTe, CdHgSTe, HgZnSe, HgZnSeTe, HgZnSTe, III-V or IV-VI semiconductors, such as G aN, GaP, GaNP, GaNAs, GaPAs, GaAs, GaAlNP, GaAlNAs, GaAlPAs, GaInNP, GaInNAs, GaInPAs, AlN, AlNP, AlNAs, AlP, AlPAs, AlAs, InN, InNP, InP, InNAs, InPAs, InAS, InAlNP, InAlNAs, InAlPAs, PbS / ZnS or PbSe / ZnS, Group IV semiconductors such as Si, Ge, SiC and SiGe, chalcopyrite compounds, including but not limited to CuInS2, CuInSe2, CuGaS2, CuGaSe2, AgInS2, AgInSe2, AgGaS, AgGaSe2 or perovskite quantum dots with ABX3 formula, wherein A is cesium, methylammonium or methylamidinium, B is lead or tin, and X is chloride, bromide or iodide.
[0023] According to one or more embodiments, the emission peak wavelength of the green fluorescent material 140 is between 500 and 570 nanometers. In some embodiments, the emission peak wavelength of the green fluorescent material 140 may be between 520 and 550 nanometers depending on the desired display effect.
[0024] According to one or more embodiments, the red fluorescent material 130 in the layered structure 110 is closer to the substrate than the green fluorescent material 140. As will be described in more detail below, various methods can be used to control the position of the red fluorescent material 130 relative to the green fluorescent material 140. After the layered structure 110 is formed, blue light can be used to pass through the substrate 120 and the layered structure 110. The blue light excites the fluorescent materials in the layered structure 110 to produce white light.
[0025] In one or more embodiments, the layered structure 110 includes a curable resin 150. The curable resin 150 can be UV-curable or thermally curable. The curable resin 150 can be an alkylphenyl silicone resin or an epoxy resin. The alkylphenyl silicone resin can be a methylphenyl silicone resin. The methylphenyl silicone resin can have different ratios of methyl and phenyl groups. As will be appreciated by those skilled in the art, the ratio of methyl to phenyl groups may depend on the desired refractive index of the curable resin 150. According to one or more embodiments, the refractive index of the curable resin 150 is 1.40 to 1.56. The ratio of methyl to phenyl groups may depend on the desired density of the curable resin. According to one or more embodiments, the density of the curable resin 150 is 1.05 to 1.15 g / cm3. Resins having properties suitable for a particular application can be selected and are readily available on the market.
[0026] The embodiments of the present disclosure relate to the Figure 1 The method for making the layered structure. The first step of the method may be to mix the red fluorescent material and the green fluorescent material with a curable resin to form an adhesive mixture. The next step of the method may be to set the adhesive mixture on a substrate. The focus of the method described here is to modify the adhesive mixture so that the red fluorescent material and the green fluorescent material form two layers on the substrate (i.e., one layer of red and one layer of green). The material with a longer wavelength is closest to the substrate, and the material with a shorter wavelength is farther away from the substrate. The modification of the adhesive mixture and thus the stratification is completed by centrifugation. The position of gravity sedimentation of different fluorescent materials during centrifugation can be controlled by appropriately selecting the size or density of each fluorescent material and the curable resin to form a layered structure. After centrifugation, the last step of the method is to cure the layered structure onto the substrate. In the layered structure finally formed by this method, the red fluorescent material is closer to the substrate than the green fluorescent material.
[0027] The layering control of different fluorescent materials is based on the sedimentation velocity as described in Equation 1 below.
[0028]
[0029] In formula 1, ui is the sedimentation velocity, d is the diameter, g is the gravity constant, ρi is the density of the fluorescent material, ρ is the density of the curable resin, and ξ is the drag coefficient. Regarding particle size, when the diameter of the red fluorescent material (d 红) is larger than the diameter of the green fluorescent material (d 绿 ), the sedimentation rate of the red fluorescent material may be higher than that of the green fluorescent material. This may cause the red fluorescent material to be closer to the substrate in the layered structure. A similar effect can be seen in terms of density, when the density of the red fluorescent material minus the density of the curable resin (ρ 红 -ρ) is greater than the density of the green fluorescent material minus the density of the curable resin (ρ 绿 -ρ), the sedimentation velocity of the red fluorescent material may be higher, resulting in delamination closer to the substrate. Regarding the drag coefficient, a larger drag coefficient is positively correlated with a higher sedimentation velocity, and the fluorescent material with a larger drag coefficient may be closer to the substrate.
[0030] In one or more embodiments, the method for making a layered structure is first to mix a red fluorescent material and a green fluorescent material with a curable resin to generate an adhesive mixture. The red fluorescent material and the green fluorescent material are as described above. According to the total weight of the adhesive mixture, the red fluorescent material can be added to the adhesive mixture at a concentration of 5-40 weight percent (wt%). The lower limit of the concentration of the red fluorescent material can be 5wt%, 10wt%, 15wt% and 20wt%, and the upper limit can be 21wt%, 25wt%, 30wt% and 40wt%, wherein the lower limit can be paired with a mathematically compatible upper limit. According to the total weight of the adhesive mixture, the green fluorescent material can be added to the adhesive mixture at a concentration of 2 to 15wt%. The lower limit of the concentration of the green fluorescent material can be 2wt%, 5wt% and 7wt%, and the upper limit can be 8wt%, 10wt%, 12wt% and 15wt%, wherein any lower limit can be paired with any mathematically compatible upper limit.
[0031] Red fluorescent material, green fluorescent material and curable resin can be mixed by appropriate methods known in the art to form a uniform mixture. For example, in one or more embodiments, vacuum stirring and deaerator are used for mixing. Vacuum stirring and deaerator can be any machine known to those skilled in the art. The vacuum pressure of vacuum stirring and deaerator can be equal to or less than 5 kPa. The adhesive mixture can be mixed for 3 to 20 minutes. The conditions of vacuum stirring and deaerator can include a rotating speed of 300 to 3000 rpm and a rotation speed of 200 to 800 rpm.
[0032] In one or more embodiments, the adhesive mixture may include various additives. As will be described in detail below, the additives may be used for specific purposes in specific embodiments. The additives may be solvents, oligomeric silanes, thickeners, fumed silica particles, and combinations thereof. The additives may change the viscosity of the curable resin. According to one or more embodiments, the viscosity of the adhesive mixture at 25°C ranges from 7000 to 1 million cP (centipoise). According to one or more embodiments, the viscosity of the adhesive mixture at 25°C ranges from 500,000 to 700,000 cP (centipoise). Changing the viscosity of the curable resin may allow the curable resin to have sufficient fluidity so that the red fluorescent material is separated from the adhesive mixture and is closer to the substrate than the green fluorescent material due to centrifugation. The viscosity of the curable resin may also be changed so that the curable resin has a sufficiently high viscosity to ensure that the green fluorescent material is farther from the substrate than the red fluorescent material under centrifugation. For example, additives such as acetone, ethyl acetate, toluene, cyclohexane, oligomeric silanes, and combinations thereof may be used to adjust the viscosity. The amount of the additive may depend on the amount required to achieve a viscosity of 7000 to 1 million cP. According to one or more embodiments, the mixing ratio of the additive is 0 to 20 wt %.
[0033] In one or more embodiments, the next step of the layered structure manufacturing method is to set the adhesive mixture on the substrate. The adhesive mixture can be set in the packaging cavity of the LED bracket using a glue dispenser. The LED size of the LED bracket can be 2204, 2604, 3006, 3806, 2016, 4014, 7020, 3528 or 3030. As known to those skilled in the art, LED size is an abbreviation, so the length and width are listed. For example, 2204 is equivalent to a length of 2.2 mm and a width of 0.4 mm.
[0034] In one or more embodiments, the next step of the layered structure manufacturing method is to centrifuge the adhesive mixture to separate the red fluorescent material and the green fluorescent material in the adhesive mixture to form a layered structure. The red fluorescent material and the green fluorescent material are separated in a manner that the red fluorescent material can be layered closer to the substrate than the green fluorescent material. As shown in the figure, in one embodiment of the layered structure, the red fluorescent material is adjacent to the substrate and the green fluorescent material is adjacent to the red fluorescent material. Other embodiments of the layered structure include suspending the green fluorescent material in a curable resin (see Example 3, Figure 2 B), while the red fluorescent material forms a layer near the substrate.
[0035] According to one or more embodiments, the adhesive mixture is centrifuged. The centrifugation time may be 1 to 5 minutes. The centrifugation speed may be 500 to 4000 rpm. The centrifugation time and speed may vary depending on the type of red fluorescent material and green fluorescent material used.
[0036] During centrifugation, the red fluorescent material may be layered closer to the substrate than the green fluorescent material. This difference in sedimentation rates of the red and green fluorescent materials can be achieved through a variety of techniques, including selecting different sizes, selecting different densities, coating the materials to change the size, encapsulating the materials to change the density, adding additives to change the viscosity of the curable resin, and centrifuging at different temperatures.
[0037] According to one or more embodiments, using red fluorescent materials and green fluorescent materials of different particle sizes causes the red fluorescent material to have a higher sedimentation rate than the green fluorescent material during centrifugation, thereby forming a layer closer to the substrate. Materials with larger average particle sizes will settle to the substrate faster than materials with smaller average particle sizes. In one or more embodiments, the average particle size of the red fluorescent material is larger than the average particle size of the green fluorescent material. For example, the average particle size of the red fluorescent material can be 1.5 to 10,000 times larger than the average particle size of the green fluorescent material. The average particle size of the red fluorescent material can be any lower limit of 1.5, 10, 100, 500, 1000, 3000 and 5000 times larger than the average particle size of the green fluorescent material to any upper limit of 100, 500, 1000, 5000, 8000 and 10,000 times, wherein any lower limit can be used in combination with any mathematically compatible upper limit. The average particle size of the red fluorescent material can be 5 nanometers to 100 microns. The average particle size of the green fluorescent material can be 10 nanometers to 60 nanometers.
[0038] According to one or more embodiments, using red fluorescent materials and green fluorescent materials of different densities causes the red fluorescent material to settle faster than the green fluorescent material during centrifugation. Materials with higher density settle onto the substrate faster than materials with lower density. In one or more embodiments, the density of the red fluorescent material minus the density of the curable resin is greater than the density of the green fluorescent material minus the density of the curable resin. For example, the density of the red fluorescent material minus the density of the curable resin can be at least 1.5 times greater than the density of the green fluorescent material minus the density of the curable resin. In one or more embodiments, the density of the red fluorescent material minus the density of the curable resin is 1.0 to 2.5 g / cm3. In one or more embodiments, the density of the green fluorescent material minus the density of the curable resin is 0 to 1.5 g / cm 3 .
[0039] In one or more embodiments, before mixing, the method includes modifying the red fluorescent material with a modifying material. The selected modifying materials react with each other or react chemically with another modifying material on the surface of other particles or other red fluorescent materials, as described below. The reaction may be a click chemistry reaction or a condensation reaction. Through the click chemistry reaction or the condensation reaction, the interaction between the modifying materials may cause the aggregation of the red fluorescent material. When the red fluorescent material forms larger aggregates, the apparent particle size increases. As described above, the larger the particle size, the higher the sedimentation rate of the red particles during centrifugation.
[0040] In one or more embodiments, the modified material includes at least two functional groups capable of undergoing a click chemistry reaction. The addition of these functional groups can cause one red fluorescent material to be modified by one functional group, while another red fluorescent material is modified by a second functional group. When the two red fluorescent materials are combined together, a click chemistry reaction will occur between the two functional groups, and the functional groups will "click" together. Due to the click chemistry reaction, the apparent particle size of the red fluorescent material may increase. As described above, the increase in particle size may cause the sedimentation rate of the red fluorescent material to accelerate during centrifugation.
[0041] According to one or more embodiments, the click chemistry reaction occurs between an alkynyl group and an azide group. Therefore, the modified material can have an alkynyl group and an azide group. In other embodiments, the click chemistry reaction occurs between a trans-cyclooctenyl group and a tetrazine group. The selection of the click chemistry coating material depends on the click chemistry reaction. For example, a modified material with an alkyne is grafted on a group of red fluorescent materials. Another group of red fluorescent materials is grafted with a modified material containing an azide. The two groups of materials are mixed in an adhesive mixture. When the two groups of materials are in contact, the alkynes and the azides will "click" together, thereby increasing the apparent particle size of the red fluorescent material. In another example, a group of red fluorescent materials is divided into two parts, and the modified material with an alkyne group is grafted on a part of the fluorescent material, and the modified material with an azide is grafted on another part of the fluorescent material. The click chemistry modified material can be grafted onto the red fluorescent material through a ligand exchange process to replace some of the original ligands on the fluorescent material. In one or more embodiments, the original ligand can be replaced with propynyl-PEG4-thiol or azide-PEG-thiol. The amount of the click chemistry modification material on the red fluorescent material may be 0.3 to 3 wt %.
[0042] According to one or more embodiments, the modified material on the red fluorescent material includes a functional group that undergoes a condensation reaction with another identical functional group. In the adhesive mixture, the condensation of the modified red fluorescent materials having the same functional group may cause the red fluorescent materials to couple together. During the centrifugation process, the increased particle size may cause the red fluorescent material to settle faster than the green fluorescent material. The modified material may contain a silanol or methoxysilane group. For example, one group of red fluorescent materials may be grafted with a modified material containing silanol, and another group of red fluorescent materials may also be grafted with a modified material containing silanol. The hydroxide in the silanol may react by a condensation reaction. In another example, a group of red fluorescent materials may be divided into two parts. The silanol modified material may be grafted on one part, and the other part may be grafted with a modified material containing silanol. The condensation modified material may be grafted on the red fluorescent material through a ligand exchange process to replace some of the original ligands present on the fluorescent material. In one or more embodiments, the modifying material containing silanol or methoxysilane groups is added to the red fluorescent material at a molar ratio of about 1:1 or 5:1 of the silanol or methylsilane groups. However, a molar ratio of silanol or methoxysilane groups to red fluorescent materials of 1:2 to 2:1 or 3:1 to 20:1 may be used.
[0043] According to one or more embodiments, the modified material on the red fluorescent material includes a functional group that reacts with the inorganic oxide particles through hydroxyl condensation. The modified red fluorescent material and the inorganic oxide particles in the binder mixture undergo a hydroxyl condensation reaction, which may result in coupling of the red fluorescent material with the inorganic oxide particles. The coupling may increase the average particle size of the red fluorescent material. The increase in particle size may cause the sedimentation rate of the red fluorescent material to be faster than that of the green fluorescent material during centrifugation. The modified material may contain a silane coupling agent. For example, compounds such as -SH functional groups and -NH2 functional groups may undergo a condensation reaction with oxides on the surface of the inorganic oxide particles through hydroxyl condensation. For example, the silane coupling agent may include trimethoxysilane propanethiol, 3-aminopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, or [3-(1-piperazinyl)propyl] trimethoxysilane, and the silane coupling agent may be grafted onto the red fluorescent material through a ligand exchange process to replace some of the original ligands on the fluorescent material. In one or more embodiments, the added mass of the red fluorescent material is 10 to 1000 times the mass of the modified material.
[0044] In one or more embodiments, the adhesive mixture further includes inorganic oxide particles for reacting with the above-mentioned coating material through hydroxyl condensation. The inorganic oxide particles can be Al2O3, TiO2, ZrO2, SiO2, ZnO, ZnMgO, SnO2 or a combination thereof. As described above, the hydroxyl groups on the surface of the inorganic oxide particles can undergo hydroxyl condensation reaction with the silane coupling agent in the red fluorescent material coating material. In one or more embodiments, the added mass of the inorganic oxide particles is 1 to 10 times the mass of the red fluorescent material.
[0045] According to one or more embodiments, the coating material on the red fluorescent material is an inorganic oxide. The inorganic oxide coating may change the density of the red fluorescent material. The inorganic oxide coating may further affect the interaction with the curable resin. The density of the coated red fluorescent material minus the density of the curable resin may still be at least 1.5 times greater than the density of the green fluorescent material minus the density of the curable resin. That is, regardless of the coating material, in one or more embodiments, during the centrifugation process, the red fluorescent material layer will be closer to the substrate than the green fluorescent material layer.
[0046] The coating of the red fluorescent material with the inorganic oxide can be completed by a sol-gel method. The sol-gel method is well known to those skilled in the art, and includes dissolving a molecular precursor in water or alcohol, and converting the precursor into a gel by hydrolysis or alcoholysis by heating and stirring. According to one or more embodiments, the precursor is tetraethyl orthosilicate (TEOS), methyltriethoxysilane (MTEOS), sodium silicate, lithium silicate, potassium silicate, aluminum isopropoxide, tripropyl orthoaluminate Al(OC3H7)3 (TPOAI), alkoxy titanium, alkoxy vanadium and a combination thereof. After hydrolysis / alkaline hydrolysis, the coated red fluorescent material can be purified and dried. The resulting coating material can be Al2O3, TiO2, ZrO2, SiO2, ZnO, ZnMgO, SnO2 or a combination thereof. The amount of the inorganic oxide coating material can be 0.2 to 5wt% more than the red fluorescent material.
[0047] In one or more embodiments, the green fluorescent material may be coated with a coating material. The coating material may be selected so that the density of the green fluorescent material is reduced by the density of the curable resin. The density may be reduced by an inorganic oxide or polymer coating material.
[0048] The coating material on the green fluorescent material can be an inorganic oxide. The inorganic oxide coating can reduce the value of the density of the green fluorescent material minus the density of the curable resin. The density of the inorganic oxide prepared by the sol-gel method (described below) can be less than the density of the green fluorescent material. After being coated with the inorganic oxide, the volume of the green fluorescent material increases, but the mass does not increase significantly. Therefore, the average density of the green fluorescent material can be controlled to be lower than the density level of the uncoated fluorescent material. The coating amount may affect the reduction in density. The value of the density of the green fluorescent material coated with the inorganic oxide minus the density of the curable resin may still be at least 1.5 times lower than the value of the density of the red fluorescent material minus the density of the curable resin. In these embodiments, the red fluorescent material may be coated or not. Regardless of which inorganic oxide coating material is selected, in one or more embodiments, the red fluorescent material will be closer to the substrate than the green fluorescent material during centrifugation.
[0049] The coating of the green fluorescent material and the inorganic oxide can be completed by a sol-gel method. The inorganic oxide coating can be Al2O3, TiO2, ZrO2, SiO2, ZnO, ZnMgO, SnO2 or a combination thereof. The amount of the coating material can be 5 to 300 wt% more than the green fluorescent material.
[0050] According to one or more embodiments, the coating material on the green fluorescent material is a polymer. The polymer coating material can reduce the density of the green fluorescent material minus the curable resin compared to the red fluorescent material minus the curable resin. The polymer selected for the coating material has a lower density than the green fluorescent material. Therefore, the amount of polymer coating may reduce the effective density of the green fluorescent material. Reducing the density of the green fluorescent material with the polymer may cause the red fluorescent material to be closer to the substrate than the red fluorescent material during centrifugation.
[0051] The coating of the green fluorescent material by the polymer coating material can be accomplished by ligand exchange. The original ligand can be exchanged with a polymer ligand containing a thiol, an amino group, a carboxyl group or a phosphate as an end group. The polymer coating material on the green fluorescent material can be polyvinyl alcohol, polymethyl methacrylate, polycarbonate, an epoxy resin and a combination thereof. The selection of the polymer coating material may depend on the density ratio of the green fluorescent material to the red fluorescent material. Regardless of the type of polymer coating used, the value obtained by subtracting the density of the curable resin from the density of the green fluorescent material is at least 1.5 times the value obtained by subtracting the density of the curable resin from the density of the red fluorescent material. The amount of the polymer coating layer can account for 30wt% to 100wt% of the green fluorescent material.
[0052] According to one or more embodiments, the modified material on the green fluorescent material includes a functional group that can improve the compatibility of the green fluorescent material with the curable resin. The improved compatibility of the green fluorescent material with the curable resin can make the sedimentation rate of the green fluorescent material lower than that of the uncoated red fluorescent material. The modified material may contain a silane coupling agent or a phenyl group. The silane coupling agent or the phenyl group may improve the compatibility with the curable resin. The modified material can be connected to the green fluorescent material by ligand exchange. In one or more embodiments, the molar ratio of the coating material is 1 to 1000 times that of the green fluorescent material. In other embodiments, the added mass of the modified material is 0.1 to 5 times that of the green fluorescent material. In other embodiments, the amount of the added modified material is 5 to 20 times that of the green fluorescent material.
[0053] Instead of changing the density of the green fluorescent material, a modified material is used so that the green fluorescent material settles slower than the red fluorescent material during centrifugation. For example, a modified material containing silane interacts with the methylphenylsiloxane curing resin and remains in suspension.
[0054] According to one or more embodiments, the modified material (by grafting) on the green fluorescent material is silane. Modifying the green fluorescent material with silane can make the green fluorescent material have a stronger interaction with the curable resin. For example, the green fluorescent material can produce a stronger dispersion force, dipole-dipole interaction and / or hydrogen bond with the curable resin. In one or more embodiments, the curable resin is methyl phenyl silicone resin. During the centrifugation process, the interaction between the green fluorescent material and the curable resin may cause the red fluorescent material to be closer to the substrate than the green fluorescent material and delaminate.
[0055] Modification of green fluorescent materials with silane materials can be achieved by ligand exchange. Some original ligands can be exchanged with methylphenylsiloxanes containing mercaptan, amino, carboxyl or phosphate groups. The ratio of methyl to phenyl in methylphenylsilicone can be roughly the same as the ratio of methyl to phenyl in curable resin. A non-limiting example of silane is oligomerization mercaptan silane. The amount of silane material can account for 0.5 to 5wt% of green fluorescent material.
[0056] In one or more embodiments, before mixing, the method includes modifying the red fluorescent material and the green fluorescent material with a modifying material. As previously described, the completion of the modification process can change the size or density of the fluorescent material according to the ability of the modification. The modification can also change the electrostatic interaction with the resin. Regardless of the modifying material, according to one or more embodiments, during centrifugation, the red fluorescent material is layered closer to the substrate than the green fluorescent material.
[0057] Centrifugation can be performed at ambient temperature. However, in one or more embodiments, centrifuging the adhesive mixture at an increased or decreased temperature may be advantageous. Increasing the temperature to 50 to 120°C may cause the red fluorescent material to precipitate from the adhesive mixture. The selection of the red fluorescent material may be based on its precipitation ability within the desired temperature range. For example, the red fluorescent material may be coated with a polymer (such as polyvinyl acetate or acrylic acid-methacrylic acid copolymer) having a glass transition temperature within the temperature range. When the coated red fluorescent material is heated above the glass transition temperature, the mobility of the coated polymer chain increases, which may lead to a tendency to aggregate together. The precipitation of the red fluorescent material may increase the apparent particle size. As previously described, during centrifugation, the increase in particle size may cause the red fluorescent material to be closer to the substrate than the green fluorescent material. Lowering the temperature to -20 to 5°C may also cause the red fluorescent material to precipitate from the adhesive mixture. The selection of the red fluorescent material may be based on its precipitation ability within the desired temperature range. For example, the red fluorescent material may be coated with a long-chain branched polymer or a polymer having a glass transition temperature below 40°C. Examples of long-chain branched polymers include polyvinyl acetate or acrylic acid-methacrylic acid copolymers. Examples of low glass transition temperature polymers may include polylactic acid, polycaprolactone, or polyisobutylene. The solubility of the polymer in the adhesive mixture may be low, resulting in precipitation from the adhesive mixture. Precipitation of the red fluorescent material may increase the apparent particle size. As previously mentioned, during centrifugation, the increase in particle size may cause the red fluorescent material to be closer to the substrate than the green fluorescent material.
[0058] In one or more embodiments, the method of centrifuging the binder mixture of red fluorescent material and green fluorescent material to form a layered structure includes using a carrier. The carrier can be used as a carrier to layer the red fluorescent material onto the substrate before the green fluorescent material. For example, the selected carrier pore size is smaller than the green fluorescent material, but larger than the red fluorescent material. The carrier can adsorb the red fluorescent material into the pores so that it is layered closer to the substrate during centrifugation while blocking the green fluorescent material. The carrier can have different pore sizes depending on the average particle size or ionic charge of the red fluorescent material and the green fluorescent material.
[0059] The carrier can be a mesoporous material or a molecular sieve. The mesoporous material can be an ion exchange resin. The mesoporous material can be Al2O3, TiO2, ZrO2, SiO2, ZnO, ZnMgO or SnO2. The molecular sieve can be a silicoaluminophosphate or aluminophosphate molecular sieve. The carrier can be added at a mass ratio of 1 to 5 times the carrier to the red fluorescent material to ensure adsorption.
[0060] The method of making the layered structure can be adjusted so that the material is partially cured and inverted before forming a fully layered structure. In this embodiment, the adhesive mixture is centrifuged to separate the red fluorescent material and the green fluorescent material to form a layered structure. The centrifuged adhesive mixture can then be partially cured by pre-curing. Partial curing does not completely cure the resin, making the red fluorescent material and the green fluorescent material immobile in the layered structure. On the contrary, partial curing still allows the fluorescent materials to move to a certain extent. The partially cured adhesive mixture can then be inverted. Inverting the partially cured layered structure will cause both materials to move away from the substrate. However, the red fluorescent material is still closer to the substrate than the green fluorescent material. Inversion can produce a layered structure in which the red fluorescent material and the green fluorescent material are not adjacent to the substrate. The resulting portion of the curable resin that does not include the red fluorescent material or the green fluorescent material can realize a remote excitation structure. It is well known that the remote excitation structure can improve the stability of the fluorescent material.
[0061] Once the appropriate layers of red and green fluorescent materials are formed by any of the above techniques, the layered structure can be cured to form the layered structure of the above LED. Curing requires that the curable resin is cured on the substrate to fix the red fluorescent material and the green fluorescent material. Curing can be accomplished by baking the layered structure and the substrate in an oven. The curing time can be 0.5 to 1 hour. The curing temperature range is 80 to 120°C.
[0062] Curing can be performed by ultraviolet (UV) light. UV curing can include using acrylate, acryloxy or epoxy UV curable resins. The wavelength of UV curing can be 330 to 400 nanometers. The power of the UV light can be from 10 to 100 mW / cm 3 , with durations ranging from 10 seconds to 2 minutes.
[0063] Embodiments of the present disclosure relate to other methods for manufacturing layered structures. In these embodiments, red fluorescent material and green fluorescent material can be mixed with a curable resin to generate an adhesive mixture. The next step of the method can be to set the adhesive mixture on a substrate. The focus of the method described herein is to modify the adhesive mixture so that the red fluorescent material is closer to the substrate than the green fluorescent material. The adhesive mixture can be changed by applying an external field. Applying an external field can control the separation of the red fluorescent material and the green fluorescent material in the adhesive mixture. Then, the layered structure can be cured on the substrate. The method can produce a final layered structure in which the red fluorescent material is closer to the substrate than the green fluorescent material.
[0064] In one or more embodiments, the method for manufacturing the layered structure firstly mixes the red fluorescent material and the green fluorescent material with a curable resin to generate an adhesive mixture. The mixing of the red fluorescent material and the green fluorescent material can be as described above.
[0065] In one or more embodiments, the next step of the layered structure manufacturing method is to place the adhesive mixture on the substrate. The placing step can be as described above.
[0066] In one or more embodiments, the next step of the layered structure manufacturing method is to modify the adhesive mixture so that the red fluorescent material and the green fluorescent material are separated to form a layered structure. The separation can be controlled by applying an external field. The adhesive mixture can be changed, and it reacts to the external field to control the separation mode. As will be further described below, the change can be achieved by coating the fluorescent material with a coating material. The external field can be an electric field. The application range of the electric field is 1 to 50 volts / cm. The device for applying the electric field can be an electric field separator. The electric field separator can include several substantially parallel and spaced electrode plates so that the polarities of adjacent electrode plates are different from each other. The red and green fluorescent materials can be coated with a charged coating material to generate a response to an external electric field. For example, a fluorescent material is coated with a positively charged coating material, such as a coating material containing an amino group. Another fluorescent material can be coated with a negatively charged coating material, such as a coating material including a carboxyl group. Therefore, when an electric field is applied, the charged coating materials on the fluorescent material will cause separation according to their attraction to a negatively charged cathode or a positively charged anode. Materials coated with negatively charged coating materials will separate near the positively charged anode. Materials coated with positively charged coating materials will separate near the negatively charged cathode.
[0067] The negatively charged coating material may include an amino group. A suitable example of a coating material having an amino group is an amino-containing siloxane. The positively charged coating material may include a carboxyl group. The coating material having a carboxyl group may be a carboxyl-containing siloxane. The charged coating material is coated on the fluorescent material by ligand exchange or surface grafting. The molar ratio of the negatively charged or positively charged group may be 10 to 10,000 times that of the fluorescent material.
[0068] In other embodiments, a magnetic field is used to change the binder mixture. The binder mixture can be changed so that it reacts to the magnetic field, thereby causing the red fluorescent material and the green fluorescent material to separate. As will be described in further detail below, the change can be achieved by coupling one of the fluorescent materials with magnetic particles. The magnetic field can be applied by a magnetic separation device. The magnetic field can also be applied using a rare earth magnet (such as neodymium) or an electromagnet.
[0069] In an embodiment where a magnetic field is used to change the adhesive mixture, the adhesive mixture may include magnetic particles. When a magnetic field is applied, the magnetic particles can be used to promote the separation of red fluorescent materials and green fluorescent materials. The magnetic particles can be Fe2O3, Fe3O4, CoFe2O4, MnFe2O4, NiFe2O4, FeCo, FeNi, NdFeB, LaCo, or a combination thereof. The selection of magnetic particles may depend on the magnetization of the magnetic powder. The magnetization may be equal to or greater than 20 angstroms / gram. In one or more embodiments, superparamagnetic nanomaterials are used as magnetic particles. The magnetic particles may have a coating material to improve the light efficiency of the layered structure. Since magnetic particles are usually made of materials that absorb ultraviolet light, the coating material may be TiO2, ZnO, Al2O3, ZrO2, or any other metal oxide known in the art that can reflect ultraviolet light. The magnetic particles can be added to the adhesive mixture at a mass ratio of 0.1 to 5 times that of the red fluorescent material. In one or more embodiments, the magnetic particles and the red fluorescent material can be added to the adhesive mixture at a mass ratio of 1:1.
[0070] According to one or more embodiments, before mixing, the method of manufacturing the layered structure includes modifying the fluorescent material with a coupling material. The coupling material may include a functional group that can be grafted onto the fluorescent material. The coupling material can be a functional group that reacts with magnetic particles. Examples of coupling materials include trimethyl orthosilicate, which interacts with the fluorescent material to produce silanes on the surface. Silanes can interact with the oxide coating of the magnetic particles and control separation by applying a magnetic field. The functional groups can be modified by ligand exchange. The amount of coupling material can be 0.5-5wt% of the fluorescent material. Once suitable red and green material layers are formed, the layered structure can be cured to form the layered structure of the above-mentioned LED.
[0071] Embodiments of the present disclosure also relate to methods for making layered structures by changing the adhesive mixture using phase separation technology. The method described herein focuses on phase separation of the adhesive mixture so that the red fluorescent material is closer to the substrate than the green fluorescent material. Phase separation is achieved by using at least two phases, wherein the two phases are immiscible. One phase can be a non-polar curable resin. The second phase can be a low-density polar solvent. The method can produce a final layered structure in which the red fluorescent material is closer to the substrate than the green fluorescent material.
[0072] In one or more embodiments, when the green fluorescent material is dissolved in a low-density polar solvent, the adhesive mixture will phase separate. The red fluorescent material is dissolved in a non-polar solvent (such as a curable resin). Since the solvents are immiscible, they will separate in the adhesive mixture.
[0073] The green fluorescent material can be dissolved in a low-density polar solvent. Examples of low-density polar solvents include water, methanol, and ethanol. The green fluorescent material can be dissolved in a low-density polar solvent at a concentration of 20-50wt%. The red fluorescent material can be dispersed together with the curable resin. The green fluorescent material and the low-density solvent can produce a microemulsion in the curable resin. During the centrifugation process, since the red fluorescent material is not suspended in the microemulsion like the green fluorescent material, the red fluorescent material layer may be closer to the substrate.
[0074] According to one or more embodiments, before mixing, the method for manufacturing a layered structure includes coating a green fluorescent material in a coating material. The coating material may be a polar ligand. The polar ligand coating material may increase the solubility of the green fluorescent material in a low-density polar solvent to achieve phase separation. The polar ligand coating material may be mercaptohexanol, mercaptopropanol, cysteine, glutathione, thioglycolic acid, mercaptopropionic acid, glutaric acid, polyethyleneimine, carboxypolyethylene oxide, or a combination thereof. The green fluorescent material may be coated with the polar ligand coating material by ligand exchange. The amount of the polar ligand coating material on the green fluorescent material may be 100 to 10,000 moles more than the green fluorescent material.
[0075] In the process of mixing the polar ligand-coated green fluorescent material, the red fluorescent material and the curable resin with a low-density polar solvent, the low-density polar solvent may form a microemulsion dispersion with the curable resin. The term "microemulsion" is used to describe a fine dispersion of one liquid in another liquid, in which the liquids are immiscible. In a microemulsion, the droplets formed are only micrometers in size. The coated green fluorescent material can be dissolved in the low-density polar solvent (aqueous phase), while the red fluorescent material can be dispersed in the curable resin or non-polar solvent (oil phase). The low-density polar solvent with the green fluorescent material may precipitate on the red fluorescent material and the curable resin, resulting in phase separation. The phase separation can be further changed by centrifugation or by allowing it to settle naturally.
[0076] According to one or more embodiments, once phase separation occurs, the adhesive mixture is dried. During the drying process, the red fluorescent material can be closer to the substrate than the green fluorescent material. Drying can be accomplished by vacuum drying. The vacuum requirements may include a pressure less than or equal to 3000 Pa, a temperature greater than or equal to 100° C., and a time period of 1 to 5 hours. Once suitable layers of red and green materials are formed, the layered structure can be cured to form the layered structure of the above-mentioned LED.
[0077] Embodiments of the present disclosure may provide at least one of the following advantages. The separation of the red fluorescent material and the green fluorescent material may improve the excitation efficiency of the red fluorescent material. In addition, the separation may reduce the re-excitation of the green light by the red fluorescent material. These advantages may together improve the luminous efficiency of the LED device. Most importantly, the method described herein requires only one adhesive mixture, one layering step, and one curing step. Existing methods known in the art require at least two adhesive mixtures, two layering steps, and two curing steps per layer.
[0078] example
[0079] Example 1: Using K2SiF6:Mn 4+ Red phosphor (Denka, Japan) is used as a red fluorescent material with a particle size of 10-40 μm. CdSe / ZnS green quantum dots are used as green fluorescent materials with a particle size of 6-40 nanometers. Weigh 50 parts (by weight) of thermosetting methylphenyl silicone resin, 30 parts of red phosphor and 20 parts of green quantum dots, mix them evenly and put them into a vacuum stirring and degassing machine, and vacuum stir and degas for 7 minutes at a speed (rotation of the stirrer) of 600 rpm and a rotation speed (rotation of the adhesive container) of 500 rpm. Use a dispensing machine to seal the mixed adhesive and fill it into the packaging cavity of the LED (4014 type) bracket. Place the encapsulated LED bracket in an automatic centrifuge and centrifuge it at a speed of 1500 rpm for 3 minutes. Bake the centrifuged LED bracket in an oven at 150°C for 2 hours.
[0080] The preparation process of CdSe / ZnS green quantum dots is as follows. First, 1mmol cadmium stearate, 50g octadecene (ODE), 2g trioctylphosphine oxide (TOPO) and 2g octadecene were heated to 280°C under a nitrogen environment, and then 2mL 0.5M tin trioctylphosphine (TOP) solution was quickly injected. After the reaction was carried out for 30 seconds, it was immediately cooled to room temperature for purification. The obtained CdSe core was small in size, and the first exciton absorption peak was about 480 nanometers. Secondly, 2mmol zinc stearate, 1g oleic acid, 0.05g TOPO, 2.5g octadecene and 10g octadecene were mixed in a flask under a nitrogen environment. The mixture was heated to 300°C, and then 0.2mmol cadmium selenide core prepared in the previous step and 2mmol S-ODE (1M) were injected in sequence. The reaction was carried out for 5 minutes and then cooled to room temperature. In the third step, 0.2mmol zinc oleate and 0.2mmol S-ODE solution were added at room temperature. The temperature was raised to 250°C, reacted for 10 minutes, and then cooled to room temperature. Repeat the above steps 5 times to obtain CdSe / ZnS green quantum dots.
[0081] Example 2: CdSe / ZnS red quantum dots are used as red fluorescent materials, with an average particle size of 6 to 40 nm and a density of 4.9 g / cm 3 (The difference between the mass density of the curable resin and that of the 3 ). Sr2AlO4:Eu 2+ Green phosphor (Dalian Luming Lighting Technology Co., Ltd.) is used as green fluorescent material, and its density is 3.6g / cm 3 (The difference in mass density from the curable resin is 2.45 g / cm 3 ). Weigh 80 parts (calculated by weight) with a density of 1.15 g / cm 3 10 parts of thermosetting methylphenyl silicone resin, 10 parts of red quantum dots and 10 parts of green phosphor are mixed evenly and placed in a vacuum stirring and degassing machine, and vacuum stirring and degassing are performed for 7 minutes at a speed of 600 rpm and a rotation speed of 500 rpm. Use a dispensing machine to seal and fill the mixed adhesive into the packaging cavity of the LED (model 4014) bracket. Place the packaged LED bracket into an automatic centrifuge and centrifuge at a speed of 1200 rpm for 3 minutes. Place the centrifuged LED bracket in an oven at 150°C and bake for 2 hours.
[0082] The preparation method of CdSe / ZnS red quantum dots is as follows. First, 3mmol cadmium stearate, 10g octadecene, 2g TOPO and 2g octadecene are mixed in a flask under a nitrogen environment and heated to 280°C. Then 2mL 0.5MSe-TOP solution is quickly injected into the flask and reacted for 10 minutes. 2mL 0.5M Se-TOP solution is added dropwise at a rate of 0.5mL / h, and then cooled to room temperature for purification. The obtained CdSe core is larger in size, and the first exciton absorption peak is about 620nm. Secondly, 2mmol zinc stearate, 1g oleic acid, 0.05g TOPO, 3g octadecene and 20g octadecene are mixed in a flask under a nitrogen environment and heated to 300°C. 0.1mmol (based on precursor) CdSe core and 2mmol S-ODE (1M) in step 1 are quickly injected into the flask in turn, react for 5 minutes and then cool to room temperature. Step 3: Add 0.2 mmol zinc oleate and 0.2 mmol S-ODE solution at room temperature, heat to 250°C, react for 10 minutes, and then cool to room temperature. Repeat the above steps 3 times to obtain CdSe / ZnS red quantum dots.
[0083] Example 3: Using K2SiF6:Mn 4+ Red phosphor is used as red fluorescent material, and its density is 3.2g / cm 3CdSe / ZnS green quantum dots were used as green fluorescent materials, where the average particle size of the quantum dots before coating was 15 nm and the density before coating was 4.2 g / cm 3 , SiO2 was coated by sol-gel method, and the average particle size after coating was 30nm±50nm, and the average density was reduced to 1.4g / cm 3 Weigh 60 parts (by weight) with a density of 1.15 g / cm 3 Thermosetting methylphenyl silicone resin, 30 parts of red phosphor and 10 parts of green SiO2 coated with quantum dots are mixed evenly and put into a vacuum stirring and degassing machine, and vacuum stirring and degassing for 7 minutes at a speed of 600 rpm and a rotation speed of 500 rpm. Use a dispensing machine to seal the mixed adhesive and fill it into the packaging cavity of the LED bracket. Put the packaged LED bracket into an automatic centrifugal sedimentation machine and centrifuge it at a speed of 1800 rpm for 5 minutes. The centrifuged LED lamp holder is baked in an oven at 150°C for 2 hours.
[0084] The coating method of CdSe / ZnS green quantum dots is as follows: 200 mg of CdSe / ZnS green quantum dots are dissolved in 100 mL of toluene, and then 2 mL of tetramethyl silicate is added, and the reaction is stirred at 60°C and 60% relative humidity for 7 days. A transparent gel is obtained, and then dried at 120°C to obtain a green quantum dot material coated with silicon oxide.
[0085] Figure 2 A and 2B are exemplary cross-sectional views of an LED package prepared by the process of Example 3 and illuminated under blue light, wherein the left view ( Figure 2 A) is a control sample without centrifugation. It can be seen that the dispersion of red and green fluorescent materials in the encapsulation adhesive is relatively uniform, and the luminous efficacy at 20mA current is 5.4lm / W. Figure 2 B) is a photo of Example 3. It can be observed that the red phosphor 220 tends to settle at the bottom of the LED surface (closest to the substrate 210) after centrifugation. The quantum dots 230 coated with green inorganic oxides do not settle significantly in the encapsulant. This optical structure can reduce the energy loss caused by the green light emitted by the quantum dots being absorbed by the red phosphor, so the light efficiency can be improved to 5.8lm / W. The relevant photos of the test method are as follows: voltage = 3V, current = 20mA, and the lighting tests are all carried out in an integrating sphere. The test method is a microscopic photo of the LED part under blue light or ultraviolet light.
[0086] Example 4: Using CdSe / ZnS red quantum dots as red fluorescent material, the density before coating is 4.3 g / cm 3 After Al2O3 coating by sol-gel method, the average density becomes 4.0g / cm 3After coating with Al2O3, the average particle size of red quantum dots is 30 to 50 nanometers. The green fluorescent material is CdSe / ZnS green quantum dots, and the density before coating is 4.2g / cm 3 After Al2O3 was coated by sol-gel method, the average density dropped to 1.4g / cm 3 Weigh 80 parts of a density of 1.15 g / cm 3 Thermosetting methylphenyl silicone resin, 10 parts of red Al2O3-coated quantum dots and 10 parts of green Al2O3-coated quantum dots are uniformly mixed in a vacuum stirring defoamer and stirred for 7 minutes at a speed of 600 rpm and a rotation speed of 500 rpm. Use a dispensing machine to seal the mixed adhesive and fill it into the packaging cavity of the LED (model 4014) bracket. Place the sealed LED bracket in an automatic centrifuge and centrifuge it at a speed of 1800 rpm for 3 minutes. Place the centrifuged LED bracket in an oven at 150°C and bake for 2 hours.
[0087] The method of coating CdSe / ZnS red and green quantum dots with Al2O3 is as follows. 200 mg of CdSe / ZnS quantum dots were dissolved in 100 mL of toluene, and then 1 mL of aluminum isopropoxide was added. The reactants were stirred at 60°C and 20% relative humidity for 7 days to form a gel, and then dried at 120°C to obtain red and green quantum dot materials coated with Al2O3.
[0088] Example 5: Select a macroporous ion exchange resin with a particle size of 10 μm and an inner pore size of 20 nm to adsorb 10-15 nm red quantum dots as red fluorescent material. CdSe / ZnS green quantum dots are used as green fluorescent material. Weigh 65 parts of a 1.15 g / cm 3 Thermosetting methylphenyl silicone resin (calculated by weight), 25 parts of red quantum dot ion exchange resin and 10 parts of green quantum dots are mixed evenly and placed in a vacuum stirring and degassing machine, and vacuum stirring and degassing is performed at a speed of 600 rpm and a rotation speed of 500 rpm for 7 minutes. Use a dispensing machine to seal the mixed adhesive and fill it into the packaging cavity of the LED (model 4014) bracket. Place the sealed LED bracket in an automatic centrifuge and centrifuge at a speed of 1500 rpm for 3 minutes. Place the centrifuged LED bracket in an oven at 150°C and bake for 2 hours.
[0089] The adsorption method of the red fluorescent material in the macroporous ion exchange resin is as follows. 200 mg of 10-15 nanometer red quantum dots are dissolved in 20 mL of toluene, and then 800 mg of a macroporous ion exchange resin with a particle size of 10 microns and an inner pore size of 20 nanometers is added. After ultrasonication or stirring for 1 hour, the solvent is removed by drying to obtain an ion exchange resin adsorbing red quantum dots.
[0090] Example 6: CdSe / ZnS red quantum dots are used as red fluorescent materials with a density of 4.3 g / cm 3 CdSe / ZnS green quantum dots were used as green fluorescent materials, with a density of 4.2 g / cm before coating. 3 After capping with terminal methacrylate mercaptomethyl by ligand exchange method, the average density dropped to 1.5 g / cm 3 . 50 parts of density 1.15g / cm 3 The thermosetting methylphenyl silicone resin, 30 parts of red phosphor and 20 parts of green methyl methacrylate coated quantum dots were weighed and mixed evenly, and then placed in a vacuum stirring and degassing machine, and vacuum stirred and degassed for 7 minutes at a speed of 600 rpm and a rotation speed of 500 rpm. Use a dispensing machine to seal the mixed adhesive and fill it into the packaging cavity of the LED (model 4014) bracket. Place the sealed LED bracket in an automatic centrifuge and centrifuge it at a speed of 1200 revolutions per minute for 3 minutes. The centrifuged LED bracket is baked in an oven at 150°C for 2 hours.
[0091] The CdSe / ZnS green quantum dots were coated with terminal mercapto methacrylate by ligand exchange method. The specific method is as follows: 200 mg of CdSe / ZnS quantum dots were dissolved in 20 mL of toluene, and then 1.2 g of terminal mercapto methacrylate was added. The reaction was stirred at 70 ° C for 12 hours. After the reaction, 50 mL of methanol was added to precipitate the reactants, and then centrifuged and dried at 70 ° C. The ligand-exchanged green quantum dots were obtained, and their average density was reduced to 1.3 g / cm 3 .
[0092] Example 7: Using CdSe / ZnS red quantum dots as red fluorescent material with a density of 4.3 g / cm 3 CdSe / ZnS green quantum dots were used as green fluorescent materials and coated on siloxane with mercapto or phenyl terminal groups (MW = 200-600) by ligand exchange method. 80 parts by weight of a 1.15 g / cm 3 Thermosetting methylphenyl silicone resin, 10 parts by weight of red quantum dots and 10 parts by weight of quantum dots coated with green siloxane are mixed evenly and placed in a vacuum stirring degassing machine, and stirred and degassed for 7 minutes at a speed of 600 rpm and a rotation speed of 500 rpm. Use a dispensing machine to seal the mixed adhesive and fill it into the packaging cavity of the LED (model 4014) bracket. Place the sealed LED bracket in an automatic centrifuge and centrifuge it at a speed of 1800 rpm for 3 minutes. The centrifuged LED bracket is baked in an oven at 150°C for 2 hours.
[0093] The CdSe / ZnS green quantum dots were coated with siloxane with mercaptomethyl terminal groups by ligand exchange. The specific steps are as follows. 200 mg of CdSe / ZnS quantum dots were dissolved in 20 mL of toluene, and then 1.8 g of terminal mercaptosiloxane was added. The reaction was stirred at 70 ° C for 12 hours. After the reaction was completed, 5 mL of methanol was added, and the precipitate was dried at 70 ° C after centrifugation to obtain ligand-exchanged green quantum dots.
[0094] Although only a few exemplary embodiments have been described in detail above, it will be readily apparent to those skilled in the art that many modifications may be made to the exemplary embodiments without substantially departing from the present invention. Therefore, all such modifications are intended to be within the scope of the present disclosure as defined in the following claims.
Claims
1. A method for manufacturing a layered structure, the method comprising: mixing a red fluorescent material and a green fluorescent material with a curable resin to prepare an adhesive mixture; disposing the adhesive mixture onto a substrate; Centrifuging the binder mixture to separate the red fluorescent material and the green fluorescent material to form a layered structure; and curing the layered structure onto the substrate. 2 . The method according to claim 1 , wherein the red fluorescent material is fluorescent powder or quantum dots, and the green fluorescent material is fluorescent powder or quantum dots.
3. The method according to any one of claims 1 to 2, wherein the curable resin is a methylphenyl silicone resin.
4. The method of any one of claims 1 to 2, wherein the centrifuging comprises centrifuging the adhesive mixture to form a centrifuged adhesive mixture; partially solidifying the centrifuged adhesive mixture to form a partially solidified centrifuged adhesive mixture; and inverting the partially solidified centrifuged adhesive mixture. 5 . The method according to claim 1 , wherein the red fluorescent material has a larger particle size than the green fluorescent material. 6 . The method according to claim 1 , wherein a value obtained by subtracting a density of the curable resin from a density of the red fluorescent material is greater than a value obtained by subtracting a density of the curable resin from a density of the green fluorescent material.
7. The method according to any one of claims 1 to 2, further comprising modifying the red fluorescent material with a modifying material before mixing.
8. The method according to claim 7, wherein the modifying material comprises an alkynyl group and an azide group, or a trans-cyclooctenyl group and a tetrazine group.
9. The method of claim 7, wherein the modifying material comprises a silane coupling agent that reacts with the inorganic oxide particles by condensation.
10. The method of claim 7, wherein the modifying material comprises an inorganic oxide.
11. The method according to any one of claims 1 to 2, further comprising coating the green fluorescent material with a coating material before mixing.
12. The method of claim 11, wherein the coating material comprises an inorganic oxide.
13. The method of claim 11, wherein the coating material comprises a polymer.
14. The method according to any one of claims 1 to 2, further comprising modifying the green fluorescent material with a modifying material before mixing.
15. The method of claim 14, wherein the modifying material comprises silane.
16. The method according to any one of claims 1 to 2, wherein the centrifugation is performed in the temperature range of 50 to 120°C or in the temperature range of -20 to 5°C or at ambient temperature.
17. The method according to any one of claims 1 to 2, wherein the red fluorescent material is located in a carrier material.
18. The method according to claim 17, wherein the support material is a mesoporous material selected from one or more of the group consisting of ion exchange resins, SiO2, TiO2, ZrO2, Al2O3, ZnO, ZnMgO, SnO2 and combinations thereof.
19. The method according to any one of claims 1 to 2, wherein the adhesive mixture further comprises an additive selected from the group consisting of one or more of a solvent, an oligomeric silane, a thickener, fumed silica particles, and combinations thereof.
20. A method of manufacturing a layered structure, the method comprising: mixing a red fluorescent material and a green fluorescent material with a curable resin to prepare an adhesive mixture; disposing the adhesive mixture onto a substrate; applying an external field to the adhesive mixture to separate the red fluorescent material and the green fluorescent material to form a layered structure; and curing the layered structure onto the substrate. 21 . The method according to claim 20 , wherein the red fluorescent material is fluorescent powder or quantum dots, and the green fluorescent material is fluorescent powder or quantum dots.
22. The method of any one of claims 20 to 21, wherein the curable resin is a methylphenyl silicone resin.
23. The method of any one of claims 20 to 21, wherein applying an external field comprises applying an electric field in the range of 1 to 50 volts per centimeter.
24. The method according to any one of claims 20 to 21, wherein the red fluorescent material and the green fluorescent material are coated with a coating material before mixing.
25. The method according to claim 24, wherein the coating material comprises a carboxyl group and an amino group, the carboxyl group is coated on one fluorescent material, and the amino group is coated on another fluorescent material.
26. The method of any one of claims 20 to 21, wherein applying an external field comprises applying a magnetic field.
27. The method of claim 26, wherein the adhesive mixture further comprises magnetic particles.
28. The method of claim 27, wherein prior to mixing, the red fluorescent material is modified with a silane coupling agent, the silane coupling agent reacting with the magnetic particles.
29. A method of manufacturing a layered structure, the method comprising: mixing a red fluorescent material and a green fluorescent material with a curable resin to prepare an adhesive mixture; disposing the adhesive mixture onto a substrate; Phase-separating the binder mixture to separate the red fluorescent material and the green fluorescent material to form a layered structure; and curing the layered structure onto the substrate.
30. The method of claim 29, wherein the red fluorescent material is quantum dots or the green fluorescent material is quantum dots.
31. The method of any one of claims 29 to 30, wherein the curable resin is methylphenyl silicone resin.
32. The method according to any one of claims 29 to 30, further comprising, before mixing, coating the green fluorescent material with a polar ligand so that the green fluorescent material is dissolved in a polar solvent.
33. The method of any one of claims 29 to 30, further comprising drying the binder mixture after the phase separation.